Evaluasi Penegakan Hukum Pidana Pemilu dalam Penyelenggaraan Pemilu 2019 - Muhammad Nur Ramadhan (Badan Pengawas Pemilihan Umum, 2019)
This paper will analyze the implementation of alleged treatment of election crimes in the implementation of election 2019. There are several weaknesses in the handling of alleged election crimes through the Integrated Law Enforcement Center (Sentra GAKKUMDU), first related to differences in understanding among the elements in Sentra Gakkumdu and both patterns of relations between Sentra Gakkumdu, become One of the obstacles indicators in election criminal law enforcement.On the other hand, there are challenges that should be promptly responded in the future democracy process, which is about the electoral law enforcement through the Sentra Gakkumdu which is still a big question in Democracy journey in Indonesia. Findings in the election 2019, there is a weakness of the electoral law enforcement, it is reflected in some cases that are handled through the Sentra Gakkumdu namely the termination of the declaration of Governor and 5 (five) regional head supports one of the presidential candidate in West Sulawesi (Sulbar) and the termination of cases of alleged violations in the stage of the campaign conducted by 12 (twelve) regional head in West Sumatera (Sumbar). Both cases can be the benchmark to evaluate the law enforcement in the implementation of the 2019 election. Analysis in this study was written based on a quality study with a juridical approach, which is to look at a series of primary legal resources in the form of legislation, other regulations related to political parties, both from aspects Institutional and implementation of elections. In addition, this study also considers secondary legal resources in the form of related literature, with the information provided from other relevant news sources. This analysis is expected to describe in detail the problem of the electoral law in the elections faced in the 2019 election and can be the answer to the problem.